2007
DOI: 10.1038/ng2106
|View full text |Cite
|
Sign up to set email alerts
|

Variation in interleukin 7 receptor α chain (IL7R) influences risk of multiple sclerosis

Abstract: Multiple sclerosis is a chronic, often disabling, disease of the central nervous system affecting more than 1 in 1,000 people in most western countries. The inflammatory lesions typical of multiple sclerosis show autoimmune features and depend partly on genetic factors. Of these genetic factors, only the HLA gene complex has been repeatedly confirmed to be associated with multiple sclerosis, despite considerable efforts. Polymorphisms in a number of non-HLA genes have been reported to be associated with multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
304
0
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 434 publications
(342 citation statements)
references
References 23 publications
22
304
0
10
Order By: Relevance
“…Several other loci showed some evidence of association, but fell short of strict genome‐wide significance thresholds; these have been subsequently validated in larger studies. The three significant findings were simultaneously replicated in independent studies from the United Kingdom, the United States and the Nordic countries 31, 32. This opened the floodgates, with several successive studies GWAS and meta‐analysis followed in rapid succession, so that by 2011, common variants in 26 genomic loci had been associated with MS risk and independently replicated, but clearly only explained a fraction of MS risk attributable to genetic factors 33, 34, 35, 36, 37, 38, 39, 40, 41, 42.…”
Section: Genome‐wide Association Studiesmentioning
confidence: 73%
See 1 more Smart Citation
“…Several other loci showed some evidence of association, but fell short of strict genome‐wide significance thresholds; these have been subsequently validated in larger studies. The three significant findings were simultaneously replicated in independent studies from the United Kingdom, the United States and the Nordic countries 31, 32. This opened the floodgates, with several successive studies GWAS and meta‐analysis followed in rapid succession, so that by 2011, common variants in 26 genomic loci had been associated with MS risk and independently replicated, but clearly only explained a fraction of MS risk attributable to genetic factors 33, 34, 35, 36, 37, 38, 39, 40, 41, 42.…”
Section: Genome‐wide Association Studiesmentioning
confidence: 73%
“…The development of genetic maps covering much of the genome led to linkage analyses in extended MS affected families from a number of countries, primarily of European ancestry 23, 24, 25, 26, 27, 28, 29, 30, 31, 32. These validated the HLA association but showed no significant linkage to loci outside the MHC.…”
Section: Early Genetic Studiesmentioning
confidence: 99%
“…[1][2][3] Recently, also a detailed genetical analysis found associations with MS risk at different levels in the entire IL-7Ra pathway, for example, in the IL-7 gene itself and in the downstream signaling molecules TYK2 and SOCS1 involved in cytokine signaling and secretion. 4 The IL-7Ra/IL-7 axis is an interesting candidate in autoimmunity, because it is an important survival factor for CD4 and CD8 T cells, and is involved in early B-cell development.…”
Section: Introductionmentioning
confidence: 99%
“…A single study showed higher IL-7 mRNA levels in the mononuclear cells in CSF of MS patients compared with other neurological diseases without oligoclonal bands. 2 On the other hand only one study with MS patients in remission and during active disease exists for the protein level. 10 However, this study did not investigate IL-7 in the context of sIL-7Ra.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Only recently, with analysis of very large cohorts, non-human leukocyte antigen MS genes are starting to be unambiguously identified. [7][8][9][10][11][12][13][14] Another important concept is the sharing of risk genes between inflammatory diseases, 15 as now demonstrated for type 1 diabetes and MS genes. 12 Therefore, cross-disciplinary genetics may be rewarding.…”
Section: Introductionmentioning
confidence: 99%